2014
DOI: 10.7241/ourd.20144.71
|View full text |Cite
|
Sign up to set email alerts
|

Xeroderma Pigmentosum: A Bane in developing country – Brief report

Abstract: IntroductionXeroderma pigmentosum is a rare, genetically heterogeneous, autosomal recessive disorder characterized by photosensitivity, cutaneous pigmentary changes, premature skin ageing, and the development of various cutaneous and internal malignancies at an early age. The basic defect underlying the clinical manifestations is a nucleotide excision repair (NER) defect leading to a defective repair of DNA damaged by ultra violet (UV) radiation [1]. XP is characterized by clinical and cellular hypersensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The ulcero-budding tumor was the most common reason for consultation, in seven out of the eight cases in our series, whereas it was observed later elsewhere [1]. The first signs observed were between the age of six months and twenty-four months, as in some sources in which the age of onset was between three months and twenty-six months [12,13]. Several studies [2,14] reported the appearance of tumors between the age of two years and eight years, which was proportional in our series, in which the tumors appeared between three and five years of age.…”
Section: Discussionmentioning
confidence: 47%
“…The ulcero-budding tumor was the most common reason for consultation, in seven out of the eight cases in our series, whereas it was observed later elsewhere [1]. The first signs observed were between the age of six months and twenty-four months, as in some sources in which the age of onset was between three months and twenty-six months [12,13]. Several studies [2,14] reported the appearance of tumors between the age of two years and eight years, which was proportional in our series, in which the tumors appeared between three and five years of age.…”
Section: Discussionmentioning
confidence: 47%
“…Mild acne typically doesn’t cause hyperpigmentation. Acne lesions that have been squeezed, squashed, or penetrated will also darken and become more pigmented [ 32 ]. Some causes of hyperpigmentation include pregnancy-related birthmarks, age spots, acne scars, and a number of drugs, including antibiotics, birth control pills, antimalarials, and tricyclic antidepressants.…”
Section: Types Of Pigmentation Disordersmentioning
confidence: 99%
“…Its autosomal recessive transmission explains its relative frequency in countries where consanguinity is high and the size of families is considerable, for instance, in Morocco [3]. In 1968, Cleaver demonstrated a deficiency of UV repair of deoxyribonucleic acid (DNA) in XP cells [4], which produces hypersensitivity to ultraviolet rays and, consequently, a high risk of developing signs of "Heloderma" and poikiloderma associated with xerosis and skin fragility, sometimes evolving to infected and trailing ulcerations, as well as cutaneous malignant tumors and oculars at an early age [5]. Indeed, it has been shown that the clinical heterogeneity of this disease is linked to the existence of alteration in the genes belonging to the various classical complementation groups-XP-A to XP-G-which are distinguished by certain symptomatic and evolutionary peculiarities.…”
Section: Introductionmentioning
confidence: 99%